Uterine Leiomyomas: Are the Blood Vessels Main Culprit? - Farooq, Bushra; Haque, Anwar Ul (International Journal of Pathology, 2018)
Objective: Evaluate their histology; particularly in reference to their blood vessels and surroundingmatrix to determine the role of vascular endothelial damage in pathogenesis of leiomyomas.Methodology: 60 cases of leiomyomas were studied by two consultant histopathologistsPlace and duration of study: Combined Military Hospital & AJK Medical College, from October 2013-December 2013Results: All leiomyomas showed significant vascular changes. There was brisk angiogenesis, endothelialcell damage, exudation of plasma with organization and fibrosis.Conclusion: The vascular changes suggested hormonal effects; particularly estrogen dominance; appropriatemanagement of theses may retard the process of fibrosis and smooth muscle hyperplasia.